2016
DOI: 10.1111/cge.12848
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review of the duplication 3q syndrome and report of a patient with Currarino syndrome and de novo duplication 3q26.32‐q27.2

Abstract: Partial duplications of the long arm of chromosome 3, dup(3q), are a rare but well-described condition, sharing features of Cornelia de Lange syndrome. Around two thirds of cases are derived from unbalanced translocations, whereas pure dup(3q) have rarely been reported. Here, we provide an extensive review of the literature on dup(3q). This search revealed several patients with caudal malformations and anomalies, suggesting that caudal malformations or anomalies represent an inherent phenotypic feature of dup(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 73 publications
(146 reference statements)
2
24
0
1
Order By: Relevance
“…Therefore, pure dup(3q) is rare, and only 31 cases (25 unrelated cases) have been described until now [reviewed by Dworschak et al, 2017]. In this study, we report a pure duplication of 2 Mb at 3q26.2 not encompassing the previously proposed critical region of dup(3q) syndrome.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, pure dup(3q) is rare, and only 31 cases (25 unrelated cases) have been described until now [reviewed by Dworschak et al, 2017]. In this study, we report a pure duplication of 2 Mb at 3q26.2 not encompassing the previously proposed critical region of dup(3q) syndrome.…”
mentioning
confidence: 60%
“…The duplicated segment in the patient described here does not encompass the previously proposed critical region of 3q26.3q27 for dup(3q) syndrome [reviewed by Dworschak et al, 2017]; nevertheless, when comparing the phenotype of our patient with the clinical manifestations of the few cases of pure dup(3q) syndrome previously reported encompassing the q26.2 region ( Table 1 ), they share the main characteristics of the syndrome, including intellectual disabilitity, synophrys, wide nasal bridge, dysmorphic ears, clinodactyly, and cardiac defects.…”
Section: Discussionmentioning
confidence: 92%
“…After sonographic detection of sacral agenesis, a comparative genomic hybridization (CGH) array should be offered, especially in cases of associated malformations. The presence of an anorectal malformation is a warning sign and should prompt consideration of amniocentesis because there is an increased incidence of anorectal malformations in patients with trisomy 21 . Some chromosomal deletions or duplications have been reported in the literature: 18p11.2 deletion and 3q26.32‐q27.2 duplication .…”
Section: Item 9: Consider Cytogenetic Analysismentioning
confidence: 99%
“…While the remaining individuals with cytogenetic abnormalities identified in this population (Xp11 deletion, 2q37 deletion, 1q21 duplication, 6q21q22 deletion, 3p26 deletion, 3q26 duplication, and trisomy 21) had expected phenotypic features for the described corresponding alteration, the origin of their craniosynostosis could not be explained easily. Extensive review of the medial literature and public databases revealed occasional reports of craniosynostosis for overlapping alterations in some instances but this was insufficient to establish a direct causative link (Dworschak et al, ; Milani et al, ; Rosenfeld et al, ; Shukla et al, ; Siu et al, ; Wilson et al, ). The only instance of a recurrent alteration in this study was a 2q37 deletion (region of overlap: hg19: 239, 315, 476–242, 783, 384) seen in two individuals, one with metopic and the other with sagittal craniosynostosis.…”
Section: Phenotype and Cytogenetic Abnormalities Detected In 10 Indivmentioning
confidence: 99%